2013
DOI: 10.1371/journal.pone.0078562
|View full text |Cite
|
Sign up to set email alerts
|

Near-Infrared 808 nm Light Boosts Complex IV-Dependent Respiration and Rescues a Parkinson-Related pink1 Model

Abstract: Mitochondrial electron transport chain (ETC) defects are observed in Parkinson’s disease (PD) patients and in PD fly- and mouse-models; however it remains to be tested if acute improvement of ETC function alleviates PD-relevant defects. We tested the hypothesis that 808 nm infrared light that effectively penetrates tissues rescues pink1 mutants. We show that irradiating isolated fly or mouse mitochondria with 808 nm light that is absorbed by ETC-Complex IV acutely improves Complex IV-dependent oxygen consumpti… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

4
29
0

Year Published

2015
2015
2024
2024

Publication Types

Select...
5
3

Relationship

3
5

Authors

Journals

citations
Cited by 43 publications
(33 citation statements)
references
References 37 publications
4
29
0
Order By: Relevance
“…Recently, it has been used successfully in diverse situations including treatment of experimental Parkinson’s disease. In fly models of Parkinson’s, 808nm has been shown to improve complex IV dependent respiration, ATP production and reduce flight defects [19]. In primates where drugs that initiate the disease target mitochondria in the brain stem, 670nm light delivered via fiber optics specifically to this region when disease is initiated, results in significantly fewer clinical signs [20].…”
Section: Discussionmentioning
confidence: 99%
“…Recently, it has been used successfully in diverse situations including treatment of experimental Parkinson’s disease. In fly models of Parkinson’s, 808nm has been shown to improve complex IV dependent respiration, ATP production and reduce flight defects [19]. In primates where drugs that initiate the disease target mitochondria in the brain stem, 670nm light delivered via fiber optics specifically to this region when disease is initiated, results in significantly fewer clinical signs [20].…”
Section: Discussionmentioning
confidence: 99%
“…Isolated mitochondria from both pink1 mutant flies and PINK1 − / − mice showed increased Complex IV activity after application of 808 nm light stimulation [43]. Furthermore, we showed that the application of near infrared light in Pink1-deficient flies results in a general improvement of flying ability as well as ATP levels, mitochondrial membrane potential, and mitochondrial morphology in both muscle and dopaminergic neurons [43]. The application of near infrared light is currently being used in skin pain treatment and holds promise as a potential therapy for PD.…”
Section: Stimulation Of the Electron Transport Chain In Pd Models Witmentioning
confidence: 96%
“…Recently, two other approaches to stimulate the ETC in PD models were published that underscore this hypothesis. One is a mechanical approach whereby the application of near infrared light (808 nm) activates Complex IV activity resulting in increased mitochondrial function and locomotion in pink1 mutants and rotenone-intoxicated flies [43]. Isolated mitochondria from both pink1 mutant flies and PINK1 − / − mice showed increased Complex IV activity after application of 808 nm light stimulation [43].…”
Section: Stimulation Of the Electron Transport Chain In Pd Models Witmentioning
confidence: 99%
See 1 more Smart Citation
“…For example GST or removing Aconitase, a major mediator of ROS-induced toxicity in mitochondria are protective Kim and Yim, 2013;Whitworth et al, 2005). In addition, expression of Ret, TNF receptor-associated protein 1 (TRAP1) and near-infrared 808 nm light all turned out to improve mitochondrial function in Drosophila pink1 mutants thereby rescuing the cellular and behavioral defects in these animals Vos et al, 2013;Zhang et al, 2013). These strategies are thus paving the way to a new generation of therapeutic strategies in Pink1-dependent strategies.…”
Section: Mitochondrial Dysfunctionmentioning
confidence: 99%